CALLUS INDUCTION OF Sonchus arvensis L. AND ITS ANTIPLASMODIAL ACTIVITY - Wahyuni, Dwi Kusuma; Purnobasuki, Hery; Kuncoro, Eko P rasetyo; Ekasari, Wiwied (African Journal of Infectious Diseases (AJID), 2020)
Background: Malaria is health global problem that emphasizes the urgent need for new drugs. Tempuyung (Sonchus arvensis L.) has many potential compounds. As the plant is originally found wild, it is important to reproduce its secondary metabolites by tissue culture. The objectives of this study were to look for effective methods to induce callus from leaf explants of Sonchus arvensis L. and to test in-vitro antiplasmodial activity. Materials and Methods: The leaves and petioles cultured on Murashige and Skoog (MS) solid medium supplemented with indole acetic-3-acid (IAA), indole-3-butyric acid (IBA), naphthalene acetic acid (NAA), 2,4-dichlorophenoxyacetic acid (2,4-D) and benzyl amino purine (BAP), in light and dark incubation. The best results obtained from callus induction were then treated by sucrose with several concentrations (1- 5%). The best results from callus induction were then extracted with methanol for the antiplasmodial test by Trager and Jensen method. It against 3D7 strain of Plasmodium falciparum.Results: The combination of 1mg/L 2,4-D and 0.5 mg/L BAP in dark incubation was the best treatment for callus induction of tempuyung. It produced the best quality of callus and the shortest period for callusing. Sucrose treatment had various effects of leaves callusing but no effect for petioles callusing, whereby 4% sucrose was the best treatment for leaves callusing in dark incubation. The methanol extract of the best callus had antiplasmodial activity with IC50=0.343 µg/mL.Conclusion: Methanol extract of tempuyung callus is feasible to be developed as antimalaria drug by continuing research to the next step